Review Artikel: Teknik -Teknik Analisis Profil Mikrobiota Penyebab Karies - Ibrahim, Sukaeni; Hardjo, Marhaen (Jurnal Ilmiah Ecosystem, 2022)
Karies gigi merupakan penyakit infeksi kronis yang umum terjadi akibat bakteri kariogenik yang melekat pada gigi. Mikroorganisme kariogenik berperan penting dalam perkembangan karies. Streptococcus mutan merupakan mikroorganisme pathogen penting dalam perkembangan lesi karies. Perkembangan terbaru dalam teknologi sekuensing DNA belakangan ini telah memungkinkan untuk memetakan profil komposisi mikrobioma rongga mulut dan memberikan harapan dalam menyelesaikan penyakit menular ini. Pada penelitian ini, kami mengumpulkan data penelitian mengenai teknik analisis profil mikrobioma rongga mulut melalui mesin pencarian online Google Scholar dan Pubmed. Dan didapatkan 15 jurnal yang membahas mengenai teknik identifikasi mikrobioma rongga mulut. Teknik analisis mikrobioma rongga mulut dapat diketahui dengan jelas beserta kelebihan dan kekurangan untuk merancang penelitian lebih lanjut tentang mikrobioma penyebab terjadinya karies. Dental caries is a common chronic infectious resulting from tooth adherent cariogenic bacteria. The cariogenic microorganisms play an important part in caries development. Streptococcus mutan is an important pathogenic organism in the development of caries lesion. The development of dental caries is highly associated with the microbiota in the oral cavity. Recent developments in DNA sequencing technology have made it possible to map the compositional profile of the oral microbiome and provide hope in solving the problem on this infectious disease. The development of dental caries is closely related to the microbiota in the oral cavity. Recent developments in DNA sequencing technology have made it possible to map the compositional profile of the oral microbiome and provide hope in solving this infectious disease problem. Methode: In this study, we collected research data regarding the technique of analyzing oral microbiome profiles through the online search engines Google Scholar and Pubmed. And obtained 15 journal that discuss the identification technique of the oral microbiome Result: The oral microbiome analysis technique can be identified clearly along with its advantages and disadvantages for design further research on the microbiome that causes caries.